LALINET STATUS - STATION EXPANSION AND LIDAR RATIO SYSTEMATIC MEASUREMENTS - Landulfo, Eduardo; Lopes, Fabio; Moreira, Gregori Arruda; da Silva, Jonatan; Ristori, Pablo; Quel, Eduardo; Otero, Lidia; Vicente Pallota, Juan; Herrera, Milagros; Salvador, Jacobo; Lucas Bali, Juan; Wolfram, Eliam; et al. (My University, 2018)
LALINET is expanding regionally to guarantee spatial coverage over South and Central Americas. One of the network goals is to obtain a set of regional representative aerosol optical properties such as particle backscatter, extinction and lidar ratio. Given the North-South extension and influence of distinct airmass circulation patterns it is paramount to distinguish these optical parameters in order to gain better perfomance in radiation transfer models. A set of lidar ratio data is presented.
Keywords: Backscatter (email); Extinction (optical mineralogy); Data set